A new SOBP-formation method by superposing specially shaped Bragg curves formed by a mini-ridge filter for spot scanning in proton beam therapy. (November 2019) - Yokokawa, K.; Furusaka, M.; Matsuura, T.; Hirayama, S.; Umegaki, K.
Highlights: A new spread-out Bragg peak formation method for proton beam treatment is proposed. This is realized by using a mini-ridge filter that has specially designed shape. Any spread-out Bragg peak can be formed by the special-shape Bragg peaks thus formed. It is effective in the case of low-energy proton beam using the spot-scanning method. Greatly reduces required number of energy layers and maintains sharp distal falloff. Abstract: Purpose: We propose a new spread-out Bragg peak (SOBP) formation method for low-energy regions of spot-scanning proton therapy in order to reduce the required number of energy layers while maintaining high dose uniformity, while maintaining the distal falloff as sharp as possible. Methods: We use only one specially shaped mini-ridge filter (MRF) to create new trapezoidal Bragg curves (TBCs) from very sharp pristine Bragg curves (PBCs) of low-energy proton beams. The TBC has three pre-designed dose regions of proximal, flat-top, and distal components. These components are designed to have nearly equal depth lengths and good linearity. Then, the required SOBP is formed by superposing the TBCs with the correct spacing and beam intensity weights. We then compare the performance of the TBC-based SOBPs with those formed by PBCs. Results: The dose uniformities of the SOBP formed by the proposed method are kept within the design tolerance, and are equivalent to those of conventional SOBPs. The sharpness of the distal falloff is reasonably kept by the deepest TBC. The required number of energy layers is significantly reduced compared with that of conventional PBC-based SOBP. Conclusions: The proposed method enables shortening of the irradiation time of spot-scanning proton beam therapy in low-energy regions with a reduced number of energy layers. It can be realized by using only one specially shaped MRF, which can be easily installed at any facility.